Accelerated Weathering Performances of Furfurylated and Acetylated Bamboo Sheets - Krisdianto, Krisdianto; Vinden, Peter; Prezwloka, Simon (Wood Research Journal, 2018)
Bamboo material is a potential wood substitute given that its physical and mechanical properties are comparable with those of wood. As lignocellulose material, bamboo is also degraded for use outdoor. Two significant chemical modification for wood which may work for bamboo material are acetylation and furfurylation. This paper evaluates the weathering performance of furfurylated and acetylated bamboo sheets. Parameters studied include colour changes and contact angle after accelerated weathering process at QUV chamber. The result shows that the total colour differences (ï„ E*) of furfurylation is higher than non-modified strips, while colour differences of acetylated bamboo strips are less than nonmodified strips. To summarize, chemically modified Sheets turn grey after weathering. Slowing of lignin photo-degradation by acetylation is attributed to the acetyl groups, which limits the degradation of lignin. Treating bamboo sheets with acetic anhydride and furfuryl alcohol was found to be effective in protecting bamboo from absorbing water during weather exposure.